Characterization of maximal respiratory pressures in healthy children - Cox, D.; Verheggen, M.; Stick, S.; Hall, Graham (Karger, 2012)
Background: Measurements of maximal voluntary inspiratory (Pimax) and expiratory (Pemax) pressures are used in the management of respiratory muscle disease. There is little data on the appropriate reference range, success rates, or repeatability of Pimax and Pemax in children or on methodological factors affecting test outcomes. Objectives: To determine Pimax and Pemax in healthy children and examine which published reference equations are best suited to a contemporary population. Secondary objectives were to assess within-test repeatability and the influence of lung volumes on Pimax and Pemax. Methods: Healthy children were prospectively recruited from the community on a volunteer basis and underwent spirometry, static lung volumes, and Pimax and Pemax testing. Results: Acceptable and repeatable (to within 20%) Pimax and Pemax were obtained in 156 children, with 105 (67%) children performing both Pimax and Pemax measurements to within 10% repeatability. The reference equations of Wilson et al. [Thorax 1984;39:535–538] best matched our healthy Caucasian children. There was an inverse relationship between Pimax and the percent of total lung capacity (TLC) at which the measurement was obtained (beta coefficient –0.96; 95% CI –1.52 to –0.39; p = 0.001), whereas at lung volumes of >80% TLC Pemax was independent of lung volume (p = 0.26). Conclusion: We demonstrated that the Wilson et al. [Thorax 1984;39:535–538] reference ranges are most suited for contemporary Caucasian Australasian children. However, robust multiethnic reference equations for maximal respiratory pressures are required. This study suggests that 10% within-test repeatability criteria are feasible in clinical practice, and that the use of lung volume measurements will improve the quality of maximal respiratory pressure measurements.